Sodium channel beta1 and beta2 subunits parallel SNS/PN3 alpha-subunit changes in injured human sensory neurons. - Coward, K; Jowett, A; Plumpton, C; Powell, A; Birch, R; Tate, S; Bountra, C; Anand, P (2001)
Voltage-gated sodium channels consist of a pore-containing alpha-subunit and one or more auxiliary beta-subunits, which may modulate channel function. We previously demonstrated that sodium channel SNS/PN3 alpha-subunits were decreased in human sensory cell bodies after spinal root avulsion injury, and accumulated at injured nerve terminals in pain states. Using specific antibodies for immunohistochemistry, we have now detected sodium channel beta1 and beta2 subunits in sensory cell bodies within control human postmortem sensory ganglia (78% of small/medium (< or = 50 microm) and 68% of large (> or = 50 microm) cells); their changes in cervical sensory ganglia after avulsion injury paralleled those described for SNS/PN3 alpha-subunits. Our results suggest that alpha- and beta-subunits share common regulatory mechanisms, but present distinct targets for novel analgesics.